OVERVIEW OF COMMUNITY-BASED TOTAL SANITATION IN KEDURUS SURABAYA CITY 2024 - Jayanti, Retno Dwi; Maharani, Nine Elissa (HEARTY, 2026)
Environmental sanitation plays an important role in preventing environmental-based diseases such as diarrhea, which has increased significantly in Surabaya from 57.23% (2021), 76.7% (2022), to 92.9% (2023). One solution is the implementation of the program.Community Based Total Sanitation.(STBM) which consists of five pillars: Stop Defecating.Open Defecation, Washing Hands with Soap, Water Management.Household Food and Beverage,.Household Waste Security, and Security.Household Liquid Waste. This study aims to describe the implementation of STBM in Kedurus Village, Karang Pilang District, Surabaya. The study used a quantitative descriptive method with a survey approach on 5,854 heads of families. The results showed that 79.3% of families already had safe toilets, 98% implemented CTPS, and 99.8% managed drinking water and food properly. However, 7.4% of families had not sorted waste, and 35.6% had not managed liquid waste properly. These findings indicate that although the implementation of STBM was quite successful, improvements are still needed in waste and liquid waste management. The active involvement of the government and community as well as the role of STBM cadres need to be increased to support the sustainability of this program.